Wortmannin targeting phosphatidylinositol 3-kinase suppresses angiogenic factors in shear-stressed endothelial cells - Gomes, Anderson M. [UNESP]; Pinto, Thais S. [UNESP]; da Costa Fernandes, Célio J. [UNESP]; da Silva, Rodrigo A. [UNESP]; Zambuzzi, Willian F. [UNESP] (Wiley, 2020)
Modifications on shear stress-based mechanical forces are associated with pathophysiological susceptibility and their effect on endothelial cells (EC) needs to be better addressed looking for comprehending the cellular and molecular mechanisms. This prompted us to better evaluate the effects of shear stress in human primary venous EC obtained from the umbilical cord, using an in vitro model to mimic the laminar blood flow, reaching an intensity 1–4 Pa. First, our data shows there is a significant up-expression of phosphatidylinositol 3-kinase (PI3K) in shear-stressed cells culminating downstream with an up-phosphorylation of AKT and up-expression of MAPK-ERK, concomitant to a dynamic cytoskeleton rearrangement upon integrin subunits (α4 and ß 3) requirements. Importantly, the results show there is significant involvement of nitric oxide synthase (eNOS), nNOS, and vascular endothelial growth factors receptor 2 (VEGFR2) in shear-stressed EC, while cell cycle-related events seem to being changed. Additionally, although diminution of 5-hydroxymethylcytosine in shear-stressed EC, suggesting a global repression of genes transcription, the promoters of PI3K and eNOS genes were significantly hydroxymethylated corroborating with their respective transcriptional profiles. Finally, to better address, the pivotal role of PI3K in shear-stressed EC we have revisited these biological issues by wortmannin targeting PI3K signaling and the data shows a dependency of PI3K signaling in controlling the expression of VGFR1, VGFR2, VEGF, and eNOS, once these genes were significantly suppressed in the presence of the inhibitor, as well as transcripts from Ki67 and CDK2 genes. Finally, our data still shows a coupling between PI3K and the epigenetic landscape of shear-stressed cells, once wortmannin promotes a significant suppression of ten-11 translocation 1 (TET1), TET2, and TET3 genes, evidencing that PI3K signaling is a necessary upstream pathway to modulate TET-related genes. In this study we determined the major mechanotransduction pathway by which blood flow driven shear stress activates PI3K which plays a pivotal role on guaranteeing endothelial cell phenotype and vascular homeostasis, opening novel perspectives to understand the molecular basis of pathophysiological disorders related with the vascular system.
Keywords: angiogenesis; eNOS; methylation; PI3K; shear stress; VEGF; wortmannin